Acute effects of different alcoholic beverages on vascular endothelium, inflammatory markers and thrombosis fibrinolysis system. - Tousoulis, D; Ntarladimas, I; Antoniades, C; Vasiliadou, C; Tentolouris, C; Papageorgiou, N; Latsios, G; Stefanadis, C (2008)
BACKGROUND and AIM: Mild alcohol consumption has been associated with decreased cardiovascular risk, although the underlying mechanisms are still unclear. We compared the acute effects of several alcoholic beverages on endothelial function, inflammatory process and thrombosis/fibrinolysis system in young adults. METHODS: In this randomized intervention trial, healthy young individuals with no risk factor for atherosclerosis were randomized into 5 equally sized groups and received an equal amount of alcohol (30 g), as red wine (264 ml), white wine (264 ml), beer (633 ml), whisky (79 ml) or water (250 ml). Forearm blood flow was determined by gauge-strain plethysmography, at baseline, 1 and 4 h after alcohol intake. Levels of interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-alpha), C-reactive protein (CRP), fibrinogen (Fib), plasminogen activator inhibitor (PAI-1), von Willebrand factor (vWF) and tissue plasminogen activator (tPA) were determined at baseline and 4 h after alcohol consumption. RESULTS: Reactive hyperemia was significantly increased 1 h after beer and red wine consumption (p<0.05 for both), while it returned at baseline at 4 h (p=ns vs baseline) but remained unchanged in all the other groups. vWF was decreased in the beer and red wine groups (p<0.05 for both) only. PAI-1/tPA ratio remained unchanged only in red wine and control group. Inflammatory markers remained unchanged in all the groups. CONCLUSIONS: Acute consumption of red wine or beer improves endothelial function and decreases vWF levels, suggesting that the type of beverage may differently affect endothelial function and thrombosis/fibrinolysis system in healthy adults.